Communication Patterns in the Development of Life Skills at the Darul Fallah Islamic Boarding School in Bogor Regency - Eko Purwanto; Sumardjo sumardjo; Retno Hafsari; Cahyono Tri Wibowo (Nyimak: Journal of Communication, 2020)
This study aims to determine the pattern of communication in the process of developing life skills at the Darul Fallah Islamic Boarding School, Bogor Regency. The research method used is a case study with a qualitative approach. The results showed that the curriculum used was an integrated curriculum, namely a combination of religious material, general material, and life skills consisting of: personal skills, social skills, academic skills, and vocational skills. Personal skill development is carried out through public lectures, muhadhoroh, pencak silat, and sports. Social skill development is carried out through HISDAF which is an organization of students, muhadatsah and scouts. Academic skill development is carried out through learning the Qur’an, Hadith and the Salaf book (Yellow book). Vocational skill development is carried out through an integrated agricultural program. Linear communication patterns are actualized in general lectures and muhadhoroh (discourse) activities. Interactional communication patterns are carried out in muhadatsah (conversation) activities, learning the Qur’an, Hadith and the Salaf books. While transactional communication patterns are carried out in scouting activities, HISDAF student organizations, and agricultural education.Keywords : Life skills, linear communication, interactional communication, transactional communication ABSTRAKPenelitian ini bertujuan untuk mengetahui pola komunikasi dalam proses pengembangan life skill di Pondok Pesantren Pertanian Darul Fallah Kabupaten Bogor. Metode penelitian yang digunakan adalah studi kasus dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa kurikulum yang digunakan adalah kurikulum terpadu, yaitu gabungan materi keagamaan, materi umum, serta keterampilan (life skill) yang terdiri atas: personal skill, social skill, academic skill, dan vocational skill. Pengembangan personal skill dilakukan melalui ceramah umum, muhadhoroh, pencak silat, dan olahraga. Pengembangan social skill dilakukan melalui HISDAF yang merupakan organisasi santri, muhadatsah dan pramuka. Pengembangan academic skill dilakukan melalui pembelajaran al-Qur’an, Hadis dan kitab salaf (kitab kuning). Pengembangan vocational skill dilakukan melalui program pertanian yang terpadu. Pola komunikasi linier diaktualisasikan dalam kegiatan ceramah umum serta muhadhoroh. Pola komunikasi interaksional dilakukan dalam kegiatan muhadatsah, pembelajaran al-Qur’an, Hadis dan kitab salaf. Adapun pola komunikasi transaksional dilakukan dalam kegiatan pramuka, organisasi santri HISDAF, dan pendidikan pertanian.Kata Kunci: Life skills, komunikasi linier, komunikasi interaksional, komunikasi transaksional